Ultra-Low Power Integrated Circuit Design Circuits, Systems, and Applications - Tan, Nianxiong Nick; Li, Dongmei; Wang, Zhihua (Analog Circuits and Signal Processing, 2014)
This book describes the design of CMOS circuits for ultra-low power consumption including analog, radio frequency (RF), and digital signal processing circuits (DSP). The book addresses issues from circuit and system design to production design, and applies the ultra-low power circuits described to systems for digital hearing aids and capsule endoscope devices. Provides a valuable introduction to ultra-low power circuit design, aimed at practicing design engineers; Describes all key building blocks of ultra-low power circuits, from a systems perspective; Applies circuits and systems described to real product examples such as hearing aids and capsule endoscopes.